A UPLC-MS/MS METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF POMALIDOMIDE FROM HUMAN PLASMA - Vasanth, D. Atul; Rajkamal, B. (International Journal of Applied Pharmaceutics, 2016)
Objective: The present work aimed to develop a simple, rapid, specific and precise liquid chromatography-tandem mass spectrophotometric (LC–MS/MS) validated method for quantification of pomalidomide and internal standard (ISTD) Fluconazole in human plasma. Methods: 50 µl of 0.1% formic acid was added to plasma samples prior to liquid-liquid extraction (LLE) using 2.5 ml of ethyl acetate. Chromatographic separation was achieved on Xterra, RP18, 5 µ (50 x 4.6 mm) column using a mixture of 0.1% (v/v) formic acid in water to methanol at a ratio of 12:88, v/v as the mobile phase. The flow rate was 0.50 ml/min. The LC eluent was split, and approximately 0.1 ml/min was introduced into Tandem mass spectrometer using turbo Ion Spray interface at 325 °C. Quantitation was performed by transitions of m/z 260.1 precursor ion to the m/z 148.8 for pomalidomide and m/z 307.1/238.0 for fluconazole. Results: The concentrations of nine working standards showed linearity between 9.998 to 1009.650 ng/ml (r2 ≥ 0.9968). Chromatographic separation was achieved within 2 min. The average extraction recoveries of three quality control concentrations were 53.86% for pomalidomide and were within the acceptance limits. The coefficient of variation was ≤15% for intra-and inter-batch assays. The %CV of ruggedness ranges 1.32 to 4.03. The % stability of short term and long term stock solution stability studies was found to be 99.01% and 98.49% respectively. Conclusion: The results obtained for specificity, linearity, accuracy, precision, ruggedness and stability studies were within limits. Thus the validated economical method was applied for pharmacokinetic studies of pomalidomide.